Interacting transcriptomes revealing molecular mechanisms underlying Xa39 mediated broad spectrum resistance of rice to bacterial blight - Zhang, Bing (Elsevier, 2015)
Glycolysis is an indispensable biochemical pathway in both animals and plants and is required for almost all physiological processes. Previous studies have shown that glycolysis plays an important role in cotton fiber development process. However, the detailed mechanism by which glycolysis is regulated is still unclear. In this study, a total of 163 genes encoding different isoforms of 20 enzymes involved in the catalysis of glycolysis and fermentation were identified in diploid Asian cotton (Gossypium arboreum). These enzymes have unique subcellular localizations and phylogenies. Among these 163 genes, 125 were expressed in Asian cotton plants, but only 51 were highly expressed in elongating Asian cotton fibers. Cis-regulatory elements involved in phytohormone responses were identified in these 51 genes, suggesting that glycolysis might be regulated by phytohormones. Furthermore, the expression of fermentation-related genes and the wide distribution of cis-regulatory elements that promote anaerobic induction strongly suggested the involvement of anaerobic glycolysis in cotton fiber development, especially during the elongation process.